Development of an Edu-Tourism Module Based on QR-Code Flora Diversity in Villa Tani Indonesia to Support Students’ Flora Identification Skills - Tahri Tahri; Pipit Marianingsih; Dwi Ratnasari (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
Technology always develops to be adapted to human needs. One type of technology is educational technology, which is used as a special tool to facilitate the education and learning process, such as QR-Code. This research aimed to develop teaching tools in the form of edu-tour modules by utilizing QR-Code technology to support students’ flora identification skills. The study used the research and development (R&D) method, with the research design referring to the 3D model (Define, Design, & Develop). The research was conducted in May 2023 – May 2024 at Villa Tani Indonesia, SMAN 5 Kota Serang, and Sultan Ageng Tirtayasa University. The feasibility test based on media experts showed a value of 97.22% with a very good category, while based on material experts showed a value of 87.18% with a very good category. The student response test from class X students of SMAN 5 Kota Serang and visitors to Villa Tani Indonesia obtained a score of 88.08% in the very feasible category.